2016
DOI: 10.1007/s00436-016-5010-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-giardial therapeutic potential of dichloromethane extracts of Zingiber officinale and Curcuma longa in vitro and in vivo

Abstract: Giardiosis is one of the common parasitic diarrhoea in humans, especially in children, worldwide. Many drugs are used for its treatment, but there is evidence of drug resistance, insufficient efficacy and unpleasant side effects. Natural products are good candidates for discovering more effective anti-giardial compounds. This study evaluated the activity of extracts of Zingiber officinale (ginger) and Curcuma longa (curcumin) against Giardia lamblia in vitro and in vivo. Giardia cyst suspension was prepared fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 30 publications
6
33
0
Order By: Relevance
“…This result agreed with Amer et al(2007) [39]. On the other hand, Dyab et al 2016[40] estimated that, in vivo ginger (more effective) and curcumin extracts significantly…”
supporting
confidence: 89%
“…This result agreed with Amer et al(2007) [39]. On the other hand, Dyab et al 2016[40] estimated that, in vivo ginger (more effective) and curcumin extracts significantly…”
supporting
confidence: 89%
“…It was proven the ovicidal effect Z. officinale against Fasciola hepatica eggs by 100% at concentrations of 5 and 10 mg/mL after 48 and 24 h treatment time respectively (Moazeni and Khademolhoseini 2016). Dyab et al (2016) found that Z. officinale extract at 50 mg/mL had a higher significant effect on Giardia lamblia cyst viability after 1 h treatment. Also, antimicrobial testing of the rhizome extract of Z. officinale at the concentration of 100 mg/mL demonstrated a potential activity against four pathogenic bacteria; Escherichia coli, Staphylococcus aureus, Bacillus spp.…”
Section: Discussionmentioning
confidence: 87%
“…After 24, 48 and 72 h of treatment, stool examinations were done to evaluate the viability of cysts. One gram of feces was homogenized in 10 cc of formal saline and the viability of cysts was done by 0.1% eosin vital staining and a haemocytometer (Dyab et al ., 2016).…”
Section: Methodsmentioning
confidence: 99%